Moiré magnetism and moiré excitons in twisted CrSBr bilayers - Junyi Liu; Xu Zhang; Gang Lu (Proceedings of the National Academy of Sciences, 2025)
Moiré excitons and moiré magnetism are essential to semiconducting van der Waals magnets. In this work, we perform a comprehensive first-principles study to elucidate the interplay of electronic excitation and magnetism in twisted magnetic CrSBr bilayers. We predict a twist-induced quantum phase transition for interlayer magnetic coupling and estimate the critical twist angle below which moiré magnetism with mixed ferromagnetic and antiferromagnetic domains could emerge. Localized one-dimensional moiré excitons are stable if the interlayer coupling is ferromagnetic and become unstable if the coupling turns to antiferromagnetic. Exciton energy modulation by magnons is estimated and dependence of exciton oscillator strength on the twist angle and interlayer coupling is analyzed. An orthogonally twisted bilayer is revealed to exhibit layer-dependent, anisotropic optical transitions. Electric field is shown to induce net magnetic moments in moiré excitons, endowing them with exceedingly long lifetimes. Our work lays the foundation for using magnetic moiré bilayers in spintronic, optoelectronic, and quantum information applications.